Effect of chitosan–hydroxyapatite scaffolds seeded with cryopreserved hADMSCs on bone sialoprotein secretion - Kamadjaja, Michael Josef Kridanto; Kuntjoro, Mefina; Pratiwi, Chandrasasi Berlian; Hartanli, Audrey Luisa (Majalah Kedokteran Gigi Indonesia, 2025)
Tooth extraction can lead to alveolar bone resorption, requiring regenerative approaches using biomaterial scaffolds combined with stem cells. Chitosan–hydroxyapatite (CS–HA), a well-established scaffold that mimics the composition of human bone, combined with stem cells represents a promising strategy to promote bone formation. This study aimed to evaluate the effect of chitosan–hydroxyapatite (CS-HA) scaffolds seeded with cryopreserved human adipose-derived mesenchymal stem cells (hADMSCs) on bone sialoprotein (BSP) secretion. The hADMSCs used in this study were commercially obtained cryopreserved cells (ATCC® PCS-500-011™) and were characterized by flow cytometry. Scaffolds were fabricated using a freeze-drying method by combining chitosan and hydroxyapatite in a 1 : 1 ratio, followed by freezing at −80 °C. A post-test-only control group design was employed, consisting of 36 samples divided into three groups: positive control (CS-HA + hADMSCs + a-MEM), negative control (hADMSCs + osteogenic medium), and treatment (CS-HA + hADMSCs + osteogenic medium), and BSP levels were subsequently quantified on days 7, 14, 21, and 28 using ELISA. One-way ANOVA demonstrated a significant difference among groups (p = 0.000), with the highest BSP secretion observed in treatment group on day 14 (BSP levels 44.29 ± 2.58), followed by treatment group on day 28 (BSP levels 46.19 ± 7.64).  The significantly elevated BSP secretion in the treatment group on day 14 demonstrates osteoinductive characteristics of the CS-HA scaffold, supporting its potential application in bone tissue engineering and regeneration.